Development of Electronic Independent Learning Activity Unit (E-ILAU) Using Project-Based Learning-STEM Integrated TPACK to Improve Higher-Order Thinking Skills - Tan Zhauna Hafis Haritzah; Endang Purwaningsih; Muhammad Reyza Arief Taqwa; Febi Dwi Putri; Fatah Kurniawan (Jurnal Pendidikan Fisika Indonesia)
High-order thinking skills (HOTS) are part of 21st-century abilities. However, students still need help solving problems, especially in simple harmonic motion material, which several studies have proved to be relatively low in HOTS. Students' HOTS abilities will be trained with various learning strategies, such as a combination of teaching materials and learning models using technology. This study aims to develop an E-ILAU (Independent Learning Activity Unit Electronic) using PjBL (Project Learning)-STEM (Science, Technology, Engineering, Mathematics) integrated with TPACK (Technological Pedagogical Content Knowledge) to improve the HOTS of high school students on simple harmonic motion topics. This research and development adapts the ADDIE design with the Analysis, Design, Development, Implementation, and Evaluation stages. Data collection instruments and data analysis techniques in this study included a product validation questionnaire to determine product validity, an E-ILAU readability test questionnaire to determine product legibility before being tested, a learning implementation observation sheet to determine product practicality, and a topic of higher order thinking skills in Simple Harmonic Motion topics to find out the effectiveness of the product obtained from the pretest-posttest in terms of the results of the difference test, n-gain, and effect size. E-ILAU was implemented using a one-group pretest-posttest design. The results showed that the validity of E-ILAU was a very valid category, the readability of E-ILAU was outstanding, and the practicality of E-ILAU in learning was carried out by the lesson plan, which received a positive response from students. As well as the effectiveness of E-ILAU in the practical category of increasing higher-order thinking skills. The results showed that the PjBL-STEM-based E-ILAU integrated with TPACK was classified as valid, practical, and effective for improving the high-level thinking skills of high school students in Simple Harmonic Motion topics.